Studies on Synthesis and Antibacterial Activity of 4-(2’-hydroxy-5’-methyl-4’,6’-dibromophen-1’-yl)-6-substituted phenyl-1,2,5,6-tetrahydropyrimidine-2-thione and 6-(2’-hydroxy-5’-methyl-4’,6’-dibromophen-1’-yl)-3-acetyl-4-substituted phenyl-4,5-dihydrop - Naik, S.M.; Naik, H.B. (Asian Journal of Chemistry, 2010)
Pyrimidine-2-thiones were prepared by heating cbalcones with thiourea in ethanolic potassium, hydroxide. 3-Acetylpyrimidine-2-thiol derivatives were prepared by the reaction of pyrimidine-2-thiones with acetyl chloride. All the compounds have been screened for their antibacterial activity.